Pengaruh Intensitas Kecanduan Rokok terhadap Kesehatan Fisik Mahasiswa Perokok Aktif di Yogyakarta - Febri Ardian; Muhammad Albar Ramadhan (Jurnal Ilmu Sosial dan Humaniora, 2026)
Smoking is a behavior that is still common among college students, despite its known negative impact on physical health. The content of harmful substances such as nicotine, tar, and carbon monoxide in cigarettes has the potential to reduce lung function and disrupt the respiratory and cardiovascular systems. This study aims to analyze the effect of cigarette addiction intensity on the physical health of active college students in Yogyakarta. This study used a quantitative approach with a survey method. The subjects were active college students who were determined through a specific sampling technique. Data were collected using a questionnaire that measured the level of cigarette addiction intensity and the physical health of the respondents. Data analysis was conducted using statistical analysis techniques to determine the influence between variables. The results of this study are expected to provide an overview of the relationship between cigarette addiction intensity and the decline in physical health of college students. This research is expected to be a consideration for educational institutions and related parties in designing education programs and prevention of smoking behavior in the university environment.